Effect of pandan extract concentration to chromium (IV) removal using bacterial cellulose-pandan composites prepared by in-situ modification technique. (2020) - Muhamad, Ida Idayu; Muhamad, Siti Nur Hidayah; Salehudin, Mohd Harfiz; Zahan, Khairul Azly; Tong, Woei Yenn; Pa'e, Norhayati
Abstract: Bacterial cellulose (BC) possesses high hydrophilicity and mechanical strength which suitable for the development of film, membrane and adsorbent materials. The morphology and properties of BC can be altered during fermentation by incorporation of additives not specifically required for the growth of bacteria in the fermentation medium. Therefore, active materials can be incorporated into BC matrices to form new composites for different applications. In this research, BC was produced from a static fermentation of Acetobacter xylinum . Applying the in-situ modification technique, pandan extract (PE) was added to the fermentation medium to form bacterial cellulose-pandan (BC-P) composite. PE contains 2-acetyl-1-pyrroline (2AP) compound consists of cyclic nitrogen and ketone groups that could be functional in metals biosorption. Different percentages of PE (25–100%) were added to examine their impact on the BC yield. Then, the BC-P composites were tested with synthetic wastewater containing chromium (VI) (Cr(VI)) for its removal study. The result shows that an increased percentage of PE added during fermentation led to the increased in BC yield. Consequently, the use of BC-P composites in the Cr(VI) removal studies resulted in the enhanced of removal efficiency up to 42% higher than the native BC. In conclusion, 2AP compound was successfully incorporated into BC matrices during fermentation by in-situ modification technique to form an active BC-P composite. Hence, the newly developed BC-P composites have presented excellent potential as an alternative for heavy metal removal in wastewater treatment.